Dance the lyrics: scenic-choreographic operations with gesture, word and humor - Machado, Diego (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This article offers a reflection grounded in artistic practice as research, focusing on the choreographic proposal Dance a letra (Dance the lyrics), which investigates the relationship between gesture, song lyrics, and humor. From the perspective of artist writings, the author systematizes creative procedures developed over a trajectory marked by the intersection of dance and humor, with an emphasis on meaning-making through the friction among musical text, gesture, and choreographic composition. Conceptual references such as Roland Barthes’s Third Meaning, Hubert Godard’s Pre-Movement, and the Theory of Incoherence in humor are brought into dialogue. The results of the process can be observed in the construction of a choreographic language that employs gestural literalness to generate critical and political layers of subtext. The work reinforces laughter as both strategy and discourse and reaffirms dance as a field of thought and invention.